EFFECTS OF FAMILY SUPPORT MODERATION ON THE INFLUENCE OF ATTITUDES, SUBJECTIVE NORMS, AND SELF-EFFICACY ON ENTREPRENEURSHIP INTENTIONS - Iskandar Iskandar; Siska Anggraeni (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The study aimed to test the effect of family support moderation on the influence of attitudes, subjective norms, and self-efficacy on entrepreneurship intentions. In other words, the study wanted to test the implementation of Milton Friedman's family support concept on the implementation of Icek Ajzen's Theory of Planned Behavior (TPB). The sample in this study was 114 vocational high school (SMK) students in Indramayu Regency. The determination of the sample is done proportionally random sampling. The data was obtained through questionnaires that have been tested for validity and reliability and analyzed using regression moderation analysis techniques (ARM). The results of the analysis showed that TPB still remained relevant for identifying entrepreneurship intentions and family support was not shown to moderate the influence of attitudes, subjective norms, and self-efficacy towards entrepreneurship intentions due to the absence of significant interactions.